2016
DOI: 10.1213/ane.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malignant Hyperthermia Diagnosis in New York State Ambulatory Surgery Center Discharge Records 2002 to 2011

Abstract: The prevalence of recorded MH diagnosis in ASC patients is approximately 1 per 500,000 and varies considerably with surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…MH susceptibility is a rare disorder. Reported prevalence of MH diagnosis in studies using hospital discharge records from administrative data ranges from 0.18 per 100,000 (95% confidence interval (CI), 0.12-0.25) in ambulatory surgery center patients to 0.96 (95% CI, 0.75-1.41) in surgical inpatients [8,9]. The low frequency of MH crises and the cost of stocking dantrolene have given rise to concern about the cost-benefit of the recommendation of the Malignant Hyperthermia Association of the United States (MHAUS) that dantrolene be made immediately available (for administration within 10 min) in operating room areas, especially in facilities with a low utilization of general anesthesia and triggering agents such as maternity units [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MH susceptibility is a rare disorder. Reported prevalence of MH diagnosis in studies using hospital discharge records from administrative data ranges from 0.18 per 100,000 (95% confidence interval (CI), 0.12-0.25) in ambulatory surgery center patients to 0.96 (95% CI, 0.75-1.41) in surgical inpatients [8,9]. The low frequency of MH crises and the cost of stocking dantrolene have given rise to concern about the cost-benefit of the recommendation of the Malignant Hyperthermia Association of the United States (MHAUS) that dantrolene be made immediately available (for administration within 10 min) in operating room areas, especially in facilities with a low utilization of general anesthesia and triggering agents such as maternity units [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The apparently similar mortality with or without dantrolene may be explained by the likelihood that mortality was reduced by dantrolene in patients who met criteria for MH, whereas mortality was also low in patients for whom dantrolene was not prescribed because their symptoms were not severe enough to meet threshold criteria for MH and warrant dantrolene treatment [ 7 ], or because their MH-like episodes were misdiagnosed and actually were caused by other syndromes treated with alternative measures. A previous study suggested that only one fourth of cases recorded as MH in hospital records represented true MH cases, whereas an equal number were attributed to other conditions [ 8 , 9 ]. In our study, a secondary subgroup inspection of individual medical records of MH patients who received dantrolene revealed that 7/13 (53.8%) were “somewhat greater than likely” to meet standardized criteria for a definite MH episode [ 44 ], compared with only 1/19 (5.26%) patients coded as having MH who did not receive dantrolene.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the incidence of MH episodes range from 1:5,000 to 1:100,000 general anesthetics [ 3 , 7 ]. However, the true incidence of MH episodes in hospital is uncertain as the accuracy of discharge records which have been used to identify MH cases has been questioned [ 8 ]. For example, in a recent report of hospital billing records in which patients with a discharge diagnosis of MH were identified, only 23.4% had a likely MH episode while 23.4% had hyperthermia attributed to other causes when their medical records were reviewed by an expert panel of anesthesiologists [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Inzidenz des malignen Hyperthermiesyndroms (MHS), einer schweren Nebenwirkung auf ein halogenes volatiles Narkotikum, beträgt etwa 1 pro100.000 bis 1 pro 500.000 durchgeführte Narkosen [16][17][18]. Die genetische Disposition dürfte jedoch noch deutlich häufiger vorkommen.…”
Section: Malignes Hyperthermiesyndromunclassified